Pasar Sentral LaIno bagi Masyarakat Muna di Kota Raha - Rasmin Rasmin; Akhmad Marhadi (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aims to identify and describe the Laino Central Market for the people of Muna in the city of Raha, in the arrangement of traders selling in Laino Market there are negotiations that are not known by the local government and the government's efforts to improve the quality of Laino Market. The research method used in this study is a qualitative descriptive method. Primary data was obtained through involved observations and in-depth interviews with the parties who had been determined using purposive sumpling techniques and direct observation in the field. Secondary data were obtained from the collection and through documents from the literature related to the research topic. The results of this study are: UPTD Pasar has an important role in building a better market. However, if the market UPTD does not carry out its role properly, the situation in the market will be bad. Future plans for the Laino Market do not exist, but in order to be realized they must be adjusted to the funds that will be used later. In addition, there must be participation from the traders themselves and the community around the Laino Market, so that market development is more focused in the future